Exploring climate change, agriculture, and food planning nexus - Delgado, Cecília (2022)
This paper explores the following questions:(1) to what extent Climate Adaptive Plans and Strategies– CAPEs – include the increase of local food productionas a way to address the effects of climatechange; (2) Do they consider each step of the foodchain or solely food production; (3) How thosemeasures are transcribed to the planning rules andregulations. A selected group of 14 cities that entereda Portuguese competition ECO XXI aiming to measurecity sustainability achievements was used for empiricalexamination. Results suggest that adaptive measuresrelate to increasing local agriculture, mapping out landavailability or stress the need for local agroecologicalpractices. Moreover, CAPEs measures are predominantlyrelated to agriculture production, leaving behindsubsequent food chain activities. Central conclusionis that even if those measures are, in theory, to betranscribed into planning rules and regulations in comingyears, they remain fragile to transform reality:planner’s awareness to these topics remain insufficientand the links between food, climate and planning arestill missing, or else quite thin.